Programmed cell death of platelets during their overactivation - E. O. Artemenko; A. N. Sveshnikova; M. A. Panteleev (Онкогематология, 2015)
Programmed cell death – it is a cell death by a strictly defined mechanism with possible impact on him and, due to this, the death control, including using of pharmacological agents. Currently known many different types of cell death, but only two basic types of cell death are adequately characterized: apoptosis and programmed necrosis. Platelets are one of the key components of the blood clotting process. A group of platelets, exposing phosphatidylserine (PS), with the programmed cell death characteristics appears at their critical agonist-induced activation. This overactivation of platelets accompanied by subsequent cell death is not completely characterized cellular processes. We view the platelets overactivation in comparison with the main known types of cell death because the platelets group exposing PS is important for bloodcoagulation processes, accelerating by several orders the plasma coagulation, and important for the thrombus formation.